Analisis Persepsi Siswa Tentang Pengaruh Kelengkapan Fasilitas Bengkel Sekolah Terhadap Tingkat Kesiapan Kerja Siswa SMK Bhina Karya Karanganyar - Maulana Arbi Bantara; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2026)
This study aims to determine the positive and significant effect of students' perceptions of the completeness of school workshop facilities on the work readiness level of Grade XII students majoring in Light Vehicle Engineering at SMK Bina Karya Karanganyar. This study uses a quantitative approach with a descriptive research design. In this study, the independent variable (X) is the completeness of school workshop facilities, while the dependent variable (Y) is the level of student work readiness. The sample used in this study consisted of 70 students from Class XII TKR 1 and XII TKR 2 at SMK Bhinneka Karya Karanganyar in the 2025/2026 academic year. Data were collected using a Likert scale. The results showed that the completeness of school workshop facilities had a positive and significant effect on the level of work readiness of students in Grade XII of the Light Vehicle Engineering Department at SMK Bina Karya Karanganyar. This was proven by the t-test results with a t-value of 4.077 and a significance of 0.000 (< 0.05). The results of the coefficient of determination test show that the completeness of school workshop facilities contributes 19.6% to student work readiness, while the rest is influenced by other factors outside this study. Thus, the better the completeness of school workshop facilities, the higher the students' work readiness.